Interdependensi Ekonomi Taiwan dan Tiongkok - Erwinta Karnadewi (Fakultas Ilmu Sosial dan Ilmu Politik, 2024)
The relationship between Taiwan and China is an interesting discussion in the study of international relations. Politically, the two countries are hostile due to different perceptions of Taiwan's history and sovereign status. However, economically, both Taiwan and China play an important role. This study aims to explore the economic interdependence of the two countries, especially from 2018 to 2022. In order to find out this, the theory of complex interdependence by Robert Keohane and Joseph Nye is used. This research is based on a qualitative descriptive method that uses literature studies in reviewing its sources. The results obtained are that the interdependence of the two countries is formed due to the institutionalization of systematic economic cooperation, the use of small military resources, geographical proximity, relations between communities, and cultural and linguistic similarities.
Reuploud Repository hasyim Juni 2026 Approved by Teddy
Keywords: Taiwan; China; Interdependence; Cooperation